Implementasi Narasi Tunggal di Kementerian Energi dan Sumber Daya Mineral - Ramadani, Thoriq; Asropi, Asropi (Jurnal Inspirasi, 2021)
Presidential Instruction No. 9 of 2015 concerning Management of Public Communication mandates the Government to disseminate to the public a single narrative and other supporting data compiled by the Ministry of Communication and Information related to government policies and programs. In addition, the Government is requested to convey every Government's policies and programs across sectors and across regions to the public quickly and accurately. The research objective is to determine the implementation of a single narrative in the Ministry of Energy and Mineral Resources (EMR) in 2019. The study uses a qualitative approach with descriptive in a single narrative of the Ministry of EMR in 2019. The data consists of primary data and secondary data. Primary data in the form of meetings (focus group discussions) and interviews related to the management of a single narrative of the Ministry of EMR. While secondary data consists of a literature review in the form of journals, books and related regulations. Based on the results of research and discussion of the analysis of the implementation of a single narrative in the Ministry of EMR in 2019, it can be concluded that the implementation of a single narrative in the Ministry of EMR in 2019 has been running, as many as seven single narratives have been published. Although, it is not yet optimal, as not all units within the Ministry of EMR participate.